A whole building life-cycle assessment methodology and its application for carbon footprint analysis of U.S. commercial buildings. Issue 1 (2nd January 2023) - Zhang, Hao; Cai, Jie; Braun, James E.
Abstract : This paper presents a holistic building life-cycle assessment methodology that estimates the embodied and operational global warming potentials (GWPs) of a building covering the envelope, mechanical and lighting systems. The methodology relies on EnergyPlus to generate the use-phase energy consumption for any given building and incorporates a streamlined procedure to extract construction materials, which are used for building envelope GWP analysis. Embodied GWP accounting was performed for a representative packaged electric cooling and gas heating system and three types of lighting technologies, i.e., incandescent, compact fluorescent (CFL) and light-emitting diode (LED). The methodology was applied for carbon footprint analysis of five U.S. Department of Energy commercial building prototypes across seven climate locations. The results show that the operation phase has a dominant contribution (more than 74%) on the overall building environmental impact. LED and CFL lighting result in 45% whole-building energy consumption and 35% GWP reductions compared to incandescent lights.